Development of Practice Learning Media Based on Programmable Logic Controller - Md. Masudul Haque; Yaya Jakaria (Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
The objectives of the study were (1) to produce PLC-based Electrical Machine Practice learning media (2) to determine the performance of PLC-based Electrical Machine Practice learning media products and (3) to determine the feasibility level of PLC-based Electrical Machine Practice learning media products. This study was Research and Development which refers to the ADDIE model according to Branch. The stages in this study include analysis, design, development, implementation, and evaluation. Data collection methods used in this study were interviews, observations, and questionnaires. The instruments used in the study were the observation sheet and questionnaires. The results of this study indicated: (1) the product of learning media for Electrical Machine Practice based on PLC Schneider SR2B201FU; (2) the product of PLC-based Electrical Machine Practice learning media has good performance; (3) the product of PLC-based Electrical Machine Practice learning media has eligibility in the very feasible category to be used in learning, which is supported by the acquisition of a consecutive score of 3.65; 3.58 and 3.58 on a 4.0 scale according to the validation of material experts, media experts, and students.